2003
DOI: 10.1046/j.1526-4637.2003.03019.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acetylsalicylic Acid on Sore Throat Pain and Other Pain Symptoms Associated With Acute Upper Respiratory Tract Infection

Abstract: A B S T R A C TObjective. Acetylsalicylic acid (ASA) has been widely used for over a century to treat pain and fever associated with acute upper respiratory tract infection (URTI), but there is a lack of clinical data to support the efficacy of ASA in this disease state. The objective of this study was to investigate the efficacy and safety of ASA for the treatment of sore throat pain associated with URTI.Design. A double-blinded, placebo-controlled, parallel group design. Two hundred seventy-two patients (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 6 publications
2
49
0
4
Order By: Relevance
“…These findings are consistent with the theoretical inference from the fact that NSAIDs suppress biological responses essential to eradicate pathogens (13). Studies of naturally occurring URTIs (9)(10)(11)(12), however, did not examine the duration of URTI symptoms. An RCT showed that acetaminophen which has little anti-inflammatory activity (13) did not change the duration of fever and other symptoms (14) …”
Section: Meanwhile Denied Influences Of Nsaids On Viral Shedding Stsupporting
confidence: 80%
See 1 more Smart Citation
“…These findings are consistent with the theoretical inference from the fact that NSAIDs suppress biological responses essential to eradicate pathogens (13). Studies of naturally occurring URTIs (9)(10)(11)(12), however, did not examine the duration of URTI symptoms. An RCT showed that acetaminophen which has little anti-inflammatory activity (13) did not change the duration of fever and other symptoms (14) …”
Section: Meanwhile Denied Influences Of Nsaids On Viral Shedding Stsupporting
confidence: 80%
“…Mogabgab and Pollock (5), Hsia et al (6) and Sperber et al, (7,8) (9)(10)(11)(12), however, have uniformly focused on the severity of acute symptoms such as nasal discharge, fever, and headache, and little attention has been paid to the duration of illness. Only one study using acetaminophen which has poor antiinflammatory activity (13) evaluated the duration of symptoms among young children with fever of presumed viral origin (14).…”
Section: Upper Respiratory Tract Infections (Urtis) Are the Most Freqmentioning
confidence: 99%
“…Nasal congestion is normally one of the first symptoms to be experienced in common cold 8,9 (often concomitant with rhinorrhoea, or 'runny' nose 10,11 ), usually occurring within 1-2 days and progressing to maximum severity at 2-3 days 8,12 . Overall, common cold symptoms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Most patients have viral infections and benefit from symptomatic treatment alone [3]. Pain relief is one of the main reasons a patient with a sore throat sees a doctor, and NSAIDs such as paracetamol, ibuprofen [4], diclofenac, and acetylsalicylic acid [5] are taken, or anesthetic substances such as lidocaine are used. Additionally, substances such as chlorhexidine, with a broad antimicrobial activity, are in use [6].…”
Section: Introductionmentioning
confidence: 99%